Isolation and pathological study of Branchiomycosis from the commercial pond of common carp (Cyprinus carpio) fish, in Governorate of Duhok / Iraq - Ibrahim, Khalid Subhi (The Iraqi Journal of Veterinary Medicine, 2011)
Branchiomycosis is a fungal disease that infects fish gills. It wasidentified by isolation and histopathological changes of examined gills incommon carp fish (Cyprinus carpio) which, were obtained from fish farm inDuhok Governorate, Iraq. The infected fish were suffering from respiratorydisorders; gulping air at the water surface, rapid movement of operculum andmassive mortality, which resulted in the loss of 95% of fish pond. The gillsappear marbled appearance with necrotic areas on the localized damage gills.The causal pathogen was identified as Branchiomyces sanguinis, in which thediameter of spores and non-septated hyphae are 5-7 μm and 12 – 20 μm,respectively. In histopathological preparation, the spores and the non-septatedhyphae have been shown to be embedded in the gill tissues contained undividedand sporulating stages.